Synthesis of 5-Trifluoromethyl-Substituted (Z)-N,N-Dimethyl-N′-(pyrazin-2-yl)formimidamides from 2-Aminopyrazines, LiI/Selectfluor, FSO2CF2CO2Me and DMF under Cu Catalysis - Hu, Jiao; Li, Shengyu; Wang, Xiaolin; Zheng, Sheng-Cai; Zhao, Xiaoming (Synthesis, 2022)
The synthesis of 5-trifluoromethyl-substituted (Z)-N,N-dimethyl-N′-(pyrazin-2-yl)formimidamides via the iodination of 2-aminopyrazines with Selectfluor/LiI followed by a domino trifluoromethylation with FSO2CF2CO2Me and a condensation with DMF in the presence of CuI is realized under mild conditions. This three-step method offers CF3-substituted (Z)-N,N-dimethyl-N′-(pyrazin-2-yl)formimidamides in yields of 55–70% and with high regioselectivities. LiI serves as an iodine source, whilst DMF functions as both a solvent and a condensation reagent. The regioselectivity of these trifluoromethylation reactions is strongly dependent upon the substituent pattern on the 2-aminopyrazines. A possible mechanism for this method is also discussed.
Keywords: trifluoromethylation; pyrazines; lithium iodide; Selectfluor; regioselectivity